Aphid resistance in potato - E. E. Radchenko (Вавиловский журнал генетики и селекции)
The problem of aphid resistance of potato genetic resources is discussed. Generally, resistance to the green peach aphid (Myzus persicae Sulzer) and the potato aphid (Macrosiphum euphorbiae Thomas) is analyzed in all available literature sources. The Solanum tuberosum L. gene pool contains very few resistant forms. Accessions highly resistant to M. persicae were revealed among 36 of 86 examined wild potato species. The largest number of resistant forms was found among S. bulbocastanum Dun., S. tarijense Hawkes, S. infundibuliforme Phil., S. canasense Hawkes and S. stoloniferum Schlechtd. et Bché. The forms highly resistant to M. euphorbiae belong to 24 of 85 studied species, namely to 10 of 18 series; the species S. bulbocastanum, S. stoloniferum and S. demissum Lindl. include the maximum number of resistant forms. Wild species accessions with specific and group resistance to aphids were revealed. Glandular pubescence of leaves and stems in such species as S. polyadenium Greenm., S. tarijense and S. berthaultii Hawkes is considered as the main mechanism of resistance. Hybrids between S. tuberosum and S. berthaultii were widely used in breeding programs; however, the presence of glandular trichomes was linked to a number of undesirable characters. It is expected that association between the trichome conditioned insect resistance of S. berthaultii and undesirable agronomic traits could be overcome with the use of molecular genetic methods. Studies of the antifeedant activity of potato glycoalkaloids and their aglucons produced controversial results. In numerous works the aphid resistance of potato is connected with plant physiological state. Differences among wild potato accessions in the localization of resistance factors (leaf surface, epidermis, mesophyll, floema) were found that were indicative of differences of resistance mechanisms in the studied forms. Works on investigating induced aphid resistance in potato have great theoretical and practical significance.